OESTRUS BEHAVIOUR IN ASSAM LOCAL GOATS (Indian Journal of Animal Production and Management, 2013)
Physical and behavioural signs and intensity of oestrus were studied in 34 Assam local goats. Oestrus detection was carried out in does by exposing them to a teaser buck four times during the 24-hour period as well as by close visual observation. Observations on oestrus were recorded from 1 day before oestrus till 2 days post oestrus. Swelling of vulva and pink vaginal mucosa were the most conspicuous physical signs of oestrus and observed at night hours of the day of oestrus in frequency percentage of 87.50 and 85.71 respectively. Wagging of tail and standing to be mounted by buck constituted predominant behavioural signs of oestrus and recorded in 92.86 - 94.64 and 80.36 - 82.14 per cent observations respectively at evening to night hours of day of oestrus. Other common behavioural signs of oestrus were seeking and sniffing of male, the highest frequency percentage being 75.00 and 67.86 respectively recorded at evening hours of day of oestrus. Bleating and loss of appetite were also prominent behavioural features observed at high frequency percentage during different periods on the day of oestrus. Manifestation of oestrus was ‘intense’, ‘intermediate’ and ‘weak’ in 47.06, 35.29 and 17.65 per cent observation respectively.
Keywords: Behavioural signs; goat; intensity; physical signs